EFFECT OF PROBEM-SOLVING METHOD ON PUPILS’ ACADEMIC ACHIEVEMENT IN MATHEMATICS - Sulaimon, Jamiu Temitope; Yusuf, Muiz Olanrewaju; Yakub, Karatu Ibrahim; Syarif, Muhammad Ilham (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
This study investigated the effect of problem-solving method on pupils’ academic achievement in mathematics in Ilorin South local government area of Kwara State. The study adopted a quasi-experimental design. The sample of the study consisted of 75 basic five (5) pupils. There were two experimental groups and two control groups; a stratified random sampling technique was used to select four schools (two public and two private) in Ilorin South local government area of Kwara state. The instrument used for the data collection was the Mathematics Achievement Test (MAT) which consists of 20 multiple choice items. Four research purposes and seven research hypotheses were formulated to guide the study. These hypotheses were tested at a 0.05 level of significance. Data collected for the study were statistically analyzed using mean and ANCOVA statistical tool. The results of the study revealed that problem-solving method had significant effects on the academic pupils in mathematics. Those taught using the problem-solving method (the experimental group) outscored those in the control group. Age and school type were not significant factors. The interaction effect between the treatment (problem-solving method) and the two variables (age and school type) was not statistically significant. Based on these findings, it was recommended that basic school mathematics teachers should adopt the use of problem-solving method to teach mathematics, especially at the middle and upper basic levels. This will enhance the academic achievement of pupils and enable them to mathematize some of their daily problems.